Development of a Novel Drug Delivery System to Deliver Drugs Directly to the Colonic Mucosa, Resulting in Improved Efficacy and Reduced Systemic Exposure for the Treatment of Ulcerative Colitis. Issue 4 (7th July 2021) - Huntsman, Merodean; Lee, Shaoying N; Stylli, Jack; Stork, Cheryl; Shimizu, Jeff; Quintana, Nelson; Singh, Sharat; Wahl, Christopher; Chuang, Emil
Abstract: Despite recent drug approvals for the treatment of inflammatory bowel diseases (IBDs), there remains a high unmet need for new technologies that can increase drug efficacy by improving site-specific drug delivery while reducing systemic exposure. These technologies must address challenges with formulation; in particular, drugs that are liquid, peptides, or proteins are difficult to formulate using existing delayed and extended oral release technologies. They also have the potential to improve efficacy and reduce systemic exposure for certain drugs by delivering higher doses directly to the site of inflammation. A novel drug delivery system is being developed for delivery at a prespecified part of the gastrointestinal (GI) tract. This autonomous mechanical capsule uses an algorithm based on reflected light to deliver soluble formulations of drugs to the predefined location. This system has significant advantages over other traditional delayed release oral formulations because it functions independently of human physiological variables such as pH and transit time and can deliver liquid formulations, peptides, and proteins. Such a system can ensure a predictable high luminal drug exposure and limited degradation or systemic absorption in the upper GI tract and would therefore be ideal for treatment of disorders such as IBD and colon cancer. Video Abstract: Lay Summary: New drugs that are safer and more effective for treating inflammatory bowel disease are needed. One solution is to develop technologies like the drug delivery system capsule that can deliver drugs at the site of disease, this lessens the amount of drug reaching the bloodstream.